Adopsi Teknologi Fermentasi Jerami Padi sebagai Pakan Ternak Berdasarkan Faktor Ekonomi - Muhammad Basir Paly; Asgaf, Khaifah (Anoa: Journal of Animal Husbandry, 2026)
Adoption of rice straw fermentation technology as animal feed can improve the quality of animal feed, and have a positive impact on the production and welfare of farmers. Although research on the adoption of rice straw fermentation technology has been conducted previously, adoption based on economic factors is still limited. Therefore, this study aims to evaluate the economic factors that can be the basis for grouping the adoption of rice straw fermentation technology as cattle feed. It was conducted in Gowa and Takalar districts. Based on existing data, there are about 102 farmers who have implemented straw fermentation. This number is the population for further determination of about 35 farmers as samples. There are four variables of economic factors measured, namely farmer income, fermentation costs, number of livestock ownership, and livestock prices in the local market. Data were collected through observations and interviews using questionnaires. Data were analyzed using discriminant statistics. The results showed that farmer income, number of livestock ownership, and livestock price had a positive contribution to the adoption of fermentation technology, while fermentation costs had a negative contribution and hindered the adoption process. This study concluded that the four variables of economic factors can be used as a basis for categorizing farmers into adopter and non-adopter groups of rice straw fermentation.